Hydroelectrolytic balance of Brazilian jiu-jitsu athletes during a simulated competition - Andreato L.V.* (2016)
© 2016, Springer-Verlag Italia.Purpose: To analyze the hydroelectrolytic balance of Brazilian jiu-jitsu athletes during a simulated competition. Methods: Eight athletes were analyzed in simulated competition (four matches of 10 min). Blood lactate and rating of perceived exertion (6–20 scale) were used to infer the intensity of the matches. Blood samples were taken to determine the serum levels of osmolality, total protein and some electrolytes (chlorides, sodium, potassium, calcium, magnesium, phosphorus and iron). Results: The lactate concentration changed during the simulated competition (F7.49 = 35.5; P < 0.001; η2 = 0.85), with an increase post-match compared to the pre-match in matches 1, 2 and 4, but not for match 3. For rating of perceived exertion, no changes were found during the competition (F3.21 = 9.4; P = 0.440; η2 = 0.12). The matches did not change the osmolality, chlorides, sodium, potassium, magnesium and iron values. For total protein, a difference was observed between the time-points (F2.8; 19.6 = 4.6; P = 0.015; η2 = 0.40), with lower concentrations in pre-match 2 than pre-match 1, post-matches 2 and 3. The calcium concentration was also affected by the simulated competition (F7.49 = 4.0; P = 0.002; η2 = 0.37), with values lower in pre-match 2 than post-matches 1 and 2. The phosphorus serum was changed by matches (F3.1; 21.7 = 18.6; P < 0.001; η2 = 0.73), with post-match 1 values higher than the pre-matches 1, 2, 3 and 4 and post-match 3. The pre-match 4 values were lower than post-matches 2 and 4. Conclusion: Although there were some changes during simulated competition, important alterations in the hydroelectrolytic balance did not occur.